Interest group using electronic management system (i-GEMS) - Lee, Seah Fang (2005)
This thesis studies and analyzes the existing situation of Tunku Abdul Rahman College (TARC) in relation to academic collaboration and information sharing among its six campuses, as well as the status and limitations of TARC’s existing electronic learning application. Based on the study, an Interest Group Using Electronic Management System (i-GEMS) is proposed to serve as a platform solution in supporting the collaboration and academic information sharing that is customized to TARC’s circumstances. The i-GEMS is a web-based application that developed using ASP.NET programming language, while Unified Approach (UA) that advocates Object- Oriented Methodology (OOM) in system implementation and Unified Modeling Language (UML) for diagram modeling are selected as a guide in developing the proposed i-GEMS system. Through the i-GEMS, lecturers from different campuses can collaborate and share academic information with each other. This in turn can lead to delivery of standardized education throughout the six campuses of TARC. In addition, lecturers can broaden their knowledge other than their own fields of teaching through accessing other academic information from the i-GEMS. In short, i-GEMS is a system that advocates managing academic information through collaboration across the campuses, information sharing and learning throughout different academic modules, as well as promoting higher interaction and information sharing among the students and lecturers.